2023
DOI: 10.1039/d2nr07007c
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the effect of substitutional cation doping in the A-site of nanoscale APbI3 perovskite layers for enhanced retention and endurance in optoelectronic resistive switching for non-volatile bipolar memory devices

Abstract: The effect of substitutional cation doping in the A-site of nanoscale APbI3 perovskite layer has been systematically investigated to achieve improvement in charge-carrier dynamics and endurance of non-volatile bipolar (NVB)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Now, as the device structures operated under the negative bias region, the plotted double log J−V curve fitted with the slopes of ∼0.75 (0 < V < −0.2) and ∼0.37 (−0.2 < V < −0.33) (Figure 4g) suggests the presence of a stronger barrier near the BE as the voltage increases in the negative region due to a larger accumulation of I − ions at the BE/SL interface. Here, the photon irradiation provides extra energy to the Pb−I, causing the early breakdown of Pb−I bond 25 to influence the large amount of I − ion migration toward BE, resulting in the formation of Schottky barrier at the interface after heavy accumulation near BE. This Schottky barrier obstructs the growth of Ag CF and facilitates the dissolution of Ag CF near the BE; hence, D2 transitioned to HRS from LRS at V R = −0.33 V. The V R required to achieve HRS under white light illumination is higher than that of the devices operated under dark conditions because of the higher number of Ag CF, as more energy is required to dissolve multiple filaments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, as the device structures operated under the negative bias region, the plotted double log J−V curve fitted with the slopes of ∼0.75 (0 < V < −0.2) and ∼0.37 (−0.2 < V < −0.33) (Figure 4g) suggests the presence of a stronger barrier near the BE as the voltage increases in the negative region due to a larger accumulation of I − ions at the BE/SL interface. Here, the photon irradiation provides extra energy to the Pb−I, causing the early breakdown of Pb−I bond 25 to influence the large amount of I − ion migration toward BE, resulting in the formation of Schottky barrier at the interface after heavy accumulation near BE. This Schottky barrier obstructs the growth of Ag CF and facilitates the dissolution of Ag CF near the BE; hence, D2 transitioned to HRS from LRS at V R = −0.33 V. The V R required to achieve HRS under white light illumination is higher than that of the devices operated under dark conditions because of the higher number of Ag CF, as more energy is required to dissolve multiple filaments.…”
Section: Resultsmentioning
confidence: 99%
“…24 First and foremost, the RS characteristics of the double cation (e.g., MAFAPbX 3 )-based ReRAM depend entirely on the doping concentration of cations at the A′-site of the AA′BX 3 perovskite structure. Recently, George and Vadivel Murugan 25 examined the electrical and optical switching characteristics of multiple double-cation perovskites prepared through the microwave-assisted solvothermal route, where MAFAPbI 3 exhibits set voltage (V S ) and reset voltage (V R ) of 0.5 and −1.7 V, respectively, in dark conditions and V S /V R of 0.3/−0.7 V under light illumination. However, optimum cation doping into the AA′PbI 3 lattice is still a challenge, and systematic investigations related to the effect of doping on RS current− voltage hysteresis, endurance variability, and retention are inferior.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) have recently emerged as highly promising candidates for next-generation photovoltaics, displaying remarkable progress in power conversion efficiencies (PCEs) that approach 26.1% within a relatively short time span of less than a decade. The general APbX 3 structure of lead halide perovskites allows for variations in both the A site cations and the X site halide anions, providing a means to adjust the material properties. , Numerous studies have highlighted the advantages of incorporating mixed cations and/or anions to finely tune the optoelectronic properties of the halide perovskite structure. Compared to the conventional methylammonium lead iodide (MAPbI 3 ), mixed-cation perovskites offer the ability to obtain high efficiencies while achieving enhanced stability. By introducing a small amount of CsI into the formamidinium (FA) and methylammonium (MA) (MA/FA) mixture solutions, triple-cation PSCs can be fabricated. , Yang et al investigated the impact of cesium (Cs) on the chemical complexity of methyl-free ammonium metal halide perovskites (MHPs) and found that a relatively high Cs component ratio (approximately 30%) promotes the formation of the pure photoactive α phase. However, for MHPs to achieve high photovoltaic performance, Cs doping should be conducted at a moderate ratio .…”
Section: Introductionmentioning
confidence: 99%
“…1−6 The general APbX 3 structure of lead halide perovskites allows for variations in both the A site cations and the X site halide anions, providing a means to adjust the material properties. 7,8 Numerous studies have highlighted the advantages of incorporating mixed cations and/or anions to finely tune the optoelectronic properties of the halide perovskite structure. 9−11 Compared to the conventional methylammonium lead iodide (MAPbI 3 ), mixed-cation perovskites offer the ability to obtain high efficiencies while achieving enhanced stability.…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation of the ON and OFF data in the endurance test is substantially reduced by introducing ALD-SnO 2 . This improved endurance by insertion of ALD-SnO 2 might be related to the surface roughness and film uniformity of the FAPbI 3 layer. , Figure S6 shows the retention time to understand the nonvolatility of the δ-FAPbI 3 /ALD-SnO 2 bilayer system. The single δ-FAPbI 3 layer exhibits unstable retention (Figure S6a); however, the bilayered δ-FAPbI 3 /ALD-SnO 2 system retains well HRS and LRS for 10 4 s with a constant ON/OFF ratio of 10 2 (Figure S6b).…”
mentioning
confidence: 99%